PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PAXEL ALGORITMA UNGGUL TANGERANG SELATAN - Fauza, Ninal; Setywati Kristianti, Lily (Journal of Research and Publication Innovation, 2023)
This research aims to determine the influence of the environment and satisfaction, both partially and simultaneously, on employee performance at PT Paxel Algorithm Unggul South Tangerang. The method used in this research is a quantitative method with an associative approach. The employee population at PT Paxel Algorithm Unggul South Tangerang is 60 people. Data collection was done by means of a questionnaire. The data analysis method uses simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The research results show that: The environment has a positive and significant effect on employee performance at PT Paxel Algorithm Unggul South Tangerang. This can be proven from the simple linear regression equation Y = -0.573+ 1.014X1. The correlation value is 0.943. falls into the interpretation of 0.80 – 0.1000, meaning that the two variables have a very strong level of relationship. As for the hypothesis test, the calculated t value > t table was obtained (21.661 > 2.001) with a significant value of 0.000 < 0.05. Satisfaction has a positive and significant effect on employee performance at PT Paxel Algorithm Unggul South Tangerang, this can be proven from the linear regression equation Y = 0.537+ 1.105X2. The correlation value of 0.968 is interpreted as 0.80 – 0.1000, meaning that the two variables have a very strong level of relationship. As for the hypothesis test, the calculated t value > t table was obtained (29.225 > 2.001) with a significant value of 0.000 < 0.05. Simultaneously, Environment and Satisfaction have a positive and significant effect on Employee Performance at PT Paxel Algorithm Unggul South Tangerang, this can be proven from the equation multiple linear regression Y = -0.239 + 0.292X1 + 0.723X2. amounting to 0.970, entered in the interval 0.80 – 0.1000 Fcount value 828.493 > Ftable 3.16 with a significance level of 0.000 < 0.05.